Changes in phytoplankton size–structure alter trophic transfer in a temperate, coastal planktonic food web - Pierre Marrec; Susanne Menden‐Deuer (Limnology and Oceanography Letters)
Abstract Microzooplankton grazing is an essential parameter to predict the fate of organic matter production in planktonic food webs. To identify predictors of grazing, we leveraged a 6‐yr time series of coastal plankton growth and grazing rates across contrasting environmental conditions. Phytoplankton size–structure and trophic transfer were seasonally consistent with small phytoplankton cell dominance and low trophic transfer in summer, and large cell dominance and higher trophic transfer in winter. Departures from this pattern during two disruptive events revealed a critical link between phytoplankton size–structure and trophic transfer. An unusual summer bloom of large phytoplankton cells yielded high trophic transfer, and an atypical winter dominance of small phytoplankton resulted in seasonally atypical low trophic transfer. Environmental conditions during these events were neither seasonally atypical nor unique. Thus, phytoplankton size–structure rather than environmental conditions held a key‐role driving trophic transfer. Phytoplankton size–structure is easily measurable and could impart predictive power of food‐web structure and the fate of primary production in coastal ecosystems.